N-Hydroxy-N-Tolyl-N´ -β-Naphthyl Benzamidine Hydrochloride as a Gravimetric Reagent for the Determination of Copper(II) - Mishra, Alok; H. Mohabey, Miss (Asian Journal of Chemistry, 2010)
N-Hydroxy-N-p-tolyl-N´-β-naphthyl benzamidine hydrochloride has been used as a new reagent for gravimetric determination of Cu(II). The proposed reagent forms a buff coloured precipitate with Cu(II) in the pH range 2.5 to 10.8. The precipitate can be dried up to 200ºC without decomposition. The solid copper complex has been characterised on the basis of m.p., elemental analysis, magnetic measurements, infrared, TGA and DTA.